Towards a generic multilayer negotiation framework for efficient application provisioning in the cloud. (31st May 2017) - Omezzine, Aya; Bellamine Ben Saoud, Narjes; Tazi, Said; Cooperman, Gene
Summary: The cloud market is nowadays a complex environment where cloud application providers need to maximize their monetary profit and end users look for the most efficient services with the lowest prices. For efficient cloud provisioning, both providers and users should be satisfied in spite of their conflicting needs. Negotiation is the most flexible solution to solve conflicts and enable reaching win‐win agreements. Cloud application provisioning has 2 main properties that highly impact the negotiation decision‐making models: (1) The interdependence between the business layer and the resource layer, and (2) the dynamic provisioning context (eg, negotiators' preferences and application scheduler). Despite the importance of these 2 properties, the current negotiation models do not take these properties into account. This paper addresses both issues. We propose a multilayer negotiation framework, which also encompasses the potential for dynamic provisioning context. For that, we propose, first, a generic negotiation model dedicated to cloud provisioning. And second, we present its instantiation among cloud layers for efficient SaaS provisioning, to maximize provider profit and increase user satisfaction. The experiments show the benefits of adding negotiation to the provisioning process by improving it for provider profit, number of accepted requests, and client satisfaction.